2012
DOI: 10.1056/nejmoa1108275
|View full text |Cite
|
Sign up to set email alerts
|

Three Postpartum Antiretroviral Regimens to Prevent Intrapartum HIV Infection

Abstract: Background The safety and efficacy of adding antiretroviral drugs to standard zidovudine prophylaxis in infants of mothers with human immunodeficiency virus (HIV) infection who did not receive antenatal antiretroviral therapy (ART) because of late identification are unclear. We evaluated three ART regimens in such infants. Methods Within 48 hours after their birth, we randomly assigned formula-fed infants born to women with a peripartum diagnosis of HIV type 1 (HIV-1) infection to one of three regimens: zido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(120 citation statements)
references
References 32 publications
5
111
1
3
Order By: Relevance
“…[14][15][16] NHLS CDW data cannot measure the number of infants who receive their HIV PCR results or are initiated on ART timeously until a unique identifier for each patient is introduced so that longitudinal data such as regular viral load and CD4 + monitoring can be linked to the HIV PCR test. HIV transmission rates at later time points, viz.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] NHLS CDW data cannot measure the number of infants who receive their HIV PCR results or are initiated on ART timeously until a unique identifier for each patient is introduced so that longitudinal data such as regular viral load and CD4 + monitoring can be linked to the HIV PCR test. HIV transmission rates at later time points, viz.…”
Section: Discussionmentioning
confidence: 99%
“…All newborns (100.0%, n = 299) received either ZDV orally (81.9%, n = 245) or ZDV and nevirapine (18.1%, n = 54) orally starting within the first 4 hours of life and lasting for four weeks 13 . Only one uninfected newborn was breastfed, although all mothers were instructed not to breastfeed, and all newborns received infant milk formula until they completed six months.…”
Section: Resultsmentioning
confidence: 99%
“…Even when administered only to the exposed infant following delivery, ARVs can reduce the rate of MTCT [10]. A study conducted in Brazil and South Africa (HPTN 040) demonstrated that among infants born to HIV-infected mothers who did not receive ARV, postpartum combination ARV is significantly more effective than ZDV alone in preventing intrapartum transmission [11]. Thus, rapid testing of women of unknown HIV status during labor affords a final opportunity to reduce the risk of MTCT.…”
Section: Discussionmentioning
confidence: 99%